Impact Analysis of Local Balinese Cultural Values on Consumer Purchasing Decisions in the Global Market of Handicraft Products - Rajiv; Widodo, Slamet (Sinergi International Journal of Economics, 2023)
This study aims to explore how local cultural values in Bali influence consumer choices in the global handicraft market. As globalization allows regional products to reach international audiences, Bali's handicrafts, known for their high cultural and aesthetic value, serve as a prime example. Using a qualitative approach, this research analyzed relevant articles and documentary sources to understand how Balinese cultural values—such as spirituality and tradition—affect international consumers' purchasing decisions. The findings reveal that global buyers highly appreciate the originality and uniqueness of Balinese handicrafts, which are deeply rooted in cultural narratives that enrich the buying experience. Moreover, increasing awareness of environmental sustainability and the strategic use of social media for digital marketing have significantly boosted interest and sales. The study underscores the importance of integrating cultural values into marketing strategies and leveraging advanced digital technologies to overcome global market challenges and expand market reach. This research contributes to the understanding of how cultural heritage can be a powerful tool in global marketing and offers practical insights for artisans and marketers aiming to enhance their competitive edge.